Collaborative Governance dalam Penanganan Banjir di Desa Tanjungsari Kecamatan Cikarang Utara - Bima Ade Prayoga Setiawan; Eka Yulyana; Lina Aryani (Peneliti.net, 2021)
This study discusses related to Collaborative Governance in flood management in Tanjungsari Village, North Cikarang District. This study uses a qualitative method with the type of case study research. Data collection techniques were carried out by triangulation which included interviews, documentation and observations. Using the Collaborative Governance theory of Ansel and Gash which resulted in the finding that the initial condition that caused flooding in Tanjungsari Village, North Cikarang District, was the accumulation of garbage in Ulu River. Bekasi Regency BPBD has not been optimal in holding the main control in facilitative leadership, institutional design is still hampered in terms of legality and the Collaboration Process is considered not optimal enough, this can be seen from the collaboration with the private sector and the community who still only go through the long-distance communication process, then for cooperation with the PUPR service, there are still obstacles such as still not being able to find the right option for flood management.